Experimental investigation of squeeze flow in bearing - Tan, Vincent Rong Shun. (2009)
This project investigates the squeeze film effect of various film thicknesses between discs with spiral groove designs. Spiral groove generates pressure rise across the bearing. The pressurized film gives the bearing load stiffness and capacity.